Understanding the Women Leaders Perspective for Green Technology Innovation and Sustainable Development in Construction - Boeky, Amanda Geraldine; Rachmawati, Riani (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2025)
In recent years, construction industry has been undergoing a shift towards sustainability and green technology innovation as both are an important aspect that focus on the goals of reducing environment issues. As key-decision makers that influence others in the field of construction, women leaders play a pivotal role to put their perspective to shape the industry’s sustainable future. This study aims to understand the unique perspectives and contributions of women leaders towards the green technology innovation and sustainable development in construction sector. The method of this study used a qualitative interviews and literature analysis to gather insights and experiences from women leaders that placed in several positions in construction including architects and engineers. The findings of this study are anticipated to not only contributes to a better understanding of the critical role played by women leaders in advancing green technology innovation but also to empower women leaders to drive green innovation and sustainability in construction and overcome gender related barriers.